2002
DOI: 10.1007/s00125-002-0851-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term food restriction prevents ageing-associated central leptin resistance in wistar rats

Abstract: Aims/hypothesis. Ageing is associated with insulin and leptin resistance in mammals. These alterations might be caused by the increased adiposity associated with ageing, by ageing alone or both. We studied whether leptin resistance occurs at the central level in the Wistar rat and we aimed to discriminate between the effects of ageing from those of the increased adiposity associated with ageing. Methods. Leptin was infused intracerebroventricularly at a constant rate in young adult, old and old Wistar rats fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
77
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 25 publications
(41 reference statements)
15
77
1
2
Order By: Relevance
“…Intracerebroventricular Hormone Treatments-Intracerebroventricular leptin and insulin administrations were performed as previously described (18). Briefly, rats were anesthe-tized with i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Intracerebroventricular Hormone Treatments-Intracerebroventricular leptin and insulin administrations were performed as previously described (18). Briefly, rats were anesthe-tized with i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Leptin inhibits appetite and weight gain by decreasing orexigenic and increasing anorexigenic peptide expression in the hypo-thalamus [109]. Studies concerning direct effects of leptin on insulin sensitivity in insulin-responsive tissues such as liver, muscle, and fat have yielded contradictory results; however, there is general agreement that leptin expression and secretion are increased in obesity and that a strong correlation exists between body fat stores and leptin plasma concentrations (Table 1) [109,110,111]. Consistent with its appetitesuppressive effect, leptin expression is stimulated upon feeding and suppressed during starvation [112].…”
Section: Leptinmentioning
confidence: 99%
“…Thus, the diminution of visceral fat induced by caloric restriction could counteract the age-associated decrease in hepatic insulin action [12]. Whereas a study [13] using a caloric restriction model concluded that adiposity plays a key role in the development of leptin resistance, another group [14] has suggested that the leptin resistance is not induced by the fat-mass accumulation only. Nevertheless, as the later study has pointed out, the development of leptin resistance in caloric restricted rat could be due to leptin-independent mechanisms activated by chronic caloric restriction.…”
mentioning
confidence: 99%